Prevention of cardiorenal damage: importance of albuminuria - Ruilope, Luis M; Ortiz, Alberto; Lucia, Alejandro; Miranda, Blanca; Alvarez-Llamas, Gloria; Barderas, Maria G; Volpe, Massimo; Ruiz-Hurtado, Gema; Pitt, Bertram (European heart journal, 2023)
Graphical Abstract Graphical Abstract The chronic kidney disease (CKD) ‘blind spot’ concept establishes that most patients with CKD and mild albuminuria preceding an estimated glomerular filtration rate < 60 mL/min/1.73 m2 are not recognized nor treated. CKD will progress and 50% of functional kidney mass will be lost before diagnosis. Albuminuria is a major risk factor for the progression of cardiovascular disease (CVD), starting from values not yet considered as defining CKD. The key point is early diagnosis of CKD as a risk factor for CVD and the widespread implementation of albuminuria screening, the assessment of early biomarkers and new therapies application to control early stages of albuminuria will diminish the cardiovascular burden related to CKD. GLP1-RAs, glucagon-like peptide 1 receptor agonists; SGLT2is, sodium-glucose cotransporter-2 inhibitors; UACR, urinary albumin/creatinine ratio. Abstract Chronic kidney disease (CKD) is projected to become a leading global cause of death by 2040, and its early detection is critical for effective and timely management. The current definition of CKD identifies only advanced stages, when kidney injury has already destroyed >50% of functioning kidney mass as reflected by an estimated glomerular filtration rate <60 mL/min/1.73 m2 or a urinary albumin/creatinine ratio >six-fold higher than physiological levels (i.e. > 30 mg/g). An elevated urinary albumin-excretion rate is a known early predictor of future cardiovascular events. There is thus a ‘blind spot’ in the detection of CKD, when kidney injury is present but is undetectable by current diagnostic criteria, and no intervention is made before renal and cardiovascular damage occurs. The present review discusses the CKD ‘blind spot’ concept and how it may facilitate a holistic approach to CKD and cardiovascular disease prevention and implement the call for albuminuria screening implicit in current guidelines. Cardiorenal risk associated with albuminuria in the high-normal range, novel genetic and biochemical markers of elevated cardiorenal risk, and the role of heart and kidney protective drugs evaluated in recent clinical trials are also discussed. As albuminuria is a major risk factor for cardiovascular and renal disease, starting from levels not yet considered in the definition of CKD, the implementation of opportunistic or systematic albuminuria screening and therapy, possibly complemented with novel early biomarkers, has the potential to improve cardiorenal outcomes and mitigate the dismal 2040 projections for CKD and related cardiovascular burden.